The impact of Using Mental Maps on the 11th Graders’ English Vocabulary Learning at The Public Schools in Ramallah - Mutair, Muhammed Musa (An-Najah National University, 2020)
This study aimed to investigate the impact of using mental maps on the 11th graders’ English vocabulary learning at the public schools in Ramallah. To achieve this, the researcher applied the quasi experimental approach. The sample of the study consisted of (60) male students from the eleventh graders at Al-Bireh Secondary School for boys in Ramallah. They were split into two groups (control and experimental). The control group consisted of (30) students and the experimental group (30) students. The two groups were randomly selected. The experimental group was taught using the mental maps strategy while the control group learnt the material through the traditional teaching. The researcher applied a pre-post vocabulary test to achieve the aims of the study. The vocabulary test consisted of five questions. The data of the tests were analyzed using t-test independent sample to decide if there are significant differences between the two groups. Effect size and Eta square were also applied to measure the effect size of mental map strategy. The results of the study showed that there are statistically significant differences in the mean scores of the control and experimental groups in the vocabulary posttest in favor of the experimental group due to the use of mental map. In the light of the results of the study, the researcher recommends teachers to apply mental maps in teaching different skills in English, to change the traditional way of teaching and present new methods in teaching vocabulary. The researcher also recommends decision makers and curriculum designers to add mental maps in curricula and instructional materials. Furthermore, supervisors are recommended to develop training courses, provide, and organize materials, books, and workshops for teachers about mental maps.
Keywords: Mental Maps; Public Schools; English Vocabulary Learning